2012
DOI: 10.1530/joe-12-0072
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen and nitrogen species generation, antioxidant defenses, and β-cell function: a critical role for amino acids

Abstract: Growing evidence indicates that the regulation of intracellular reactive oxygen species (ROS) and reactive nitrogen species (RNS) levels is essential for maintaining normal β-cell glucose responsiveness. While long-term exposure to high glucose induces oxidative stress in β cells, conflicting results have been published regarding the impact of ROS on acute glucose exposure and their role in glucose stimulated insulin secretion (GSIS). Although β cells are considered to be particularly vulnerable to oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 62 publications
0
122
1
6
Order By: Relevance
“…As diabetes progresses, insulin production falls and b-cell apoptosis increases, driving further defective glycaemic control. (Lenzen 2008, Newsholme et al 2012, Cao & Kaufman 2014, Keane et al 2015. ROS and RNS can be products of mitochondrial metabolism or can be produced in the cytoplasm, for example, by the enzymes NADPH oxidase and induced nitrogen oxide synthase (iNOS).…”
Section: Oxidative and Er Stress In B-cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…As diabetes progresses, insulin production falls and b-cell apoptosis increases, driving further defective glycaemic control. (Lenzen 2008, Newsholme et al 2012, Cao & Kaufman 2014, Keane et al 2015. ROS and RNS can be products of mitochondrial metabolism or can be produced in the cytoplasm, for example, by the enzymes NADPH oxidase and induced nitrogen oxide synthase (iNOS).…”
Section: Oxidative and Er Stress In B-cell Dysfunctionmentioning
confidence: 99%
“…To regulate intracellular ROS and RNS, cells produce a range of detoxifying enzymes, and the balance between production and detoxification therefore determines intracellular ROS and RNS concentrations. Because of their high biosynthetic load and requirement for oxygen, b-cells are considered to be very sensitive to the overproduction of ROS and RNS, and oxidative stress is considered an important element of b-cell dysfunction in T2D and of b-cell depletion in T1D (Lenzen 2008, Newsholme et al 2012, Cao & Kaufman 2014, Keane et al 2015. In addition to causing ER stress, oxidative stress has multiple deleterious effects on b-cell function, including suppression of insulin transcription (Kaneto & Matsuoka 2015).…”
Section: Oxidative and Er Stress In B-cell Dysfunctionmentioning
confidence: 99%
“…The chronic intracellular accumulation of lipids, particularly in the presence of high glucose, can elicit damaging effects in b-cells through excessive reactive oxygen species (ROS) generation by increased TCA metabolite turnover, enhanced electron transport chain activity and elevated ER stress (conditions resulting in glucolipotoxicity (for further details, see review Newsholme et al (2012b))). Excessive ROS can activate key inflammation pathways including nuclear factor k-light-chain-enhancer of activated B cells (NFkB) and c-Jun NH 2 -terminal kinase (JNK) signalling (Morgan & Liu 2011).…”
Section: Lipid Metabolism and Insulin Secretionmentioning
confidence: 99%
“…The results of other studies showed that ethanol and Cd increased the serum and liver MDA concentrations 24 h after administration [4]. Haki Kara et al 2002 suggest that single doses of different concentrations of Cd are administered the dose dependent increase in MDA levels in agreement with this knowledge [35]. The levels of AOPP, CC and MG was evaluated.…”
Section: Resultsmentioning
confidence: 73%